2021
DOI: 10.1186/s12882-021-02240-1
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid tissue in early‐stage IgG4-related tubulointerstitial nephritis incidentally detected with a tumor lesion of the ureteropelvic junction: a case report

Abstract: Background IgG4-related kidney disease causes renal impairment of unknown pathogenesis that may progress to kidney failure. Although ectopic germinal centers contribute to the pathogenesis of the head and neck lesions of IgG4-related disease, the presence of tertiary lymphoid tissue (TLT) containing germinal centers in IgG4-RKD has rarely been reported. Case presentation We report a 72-year-old Japanese man who had IgG4-related tubulointerstitial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…However, the accumulation of somatic hypermutations in the IgA variable region genes cloned from these PBs suggests that they were generated via GCs in a T cell–dependent manner. Although tertiary lymphoid tissues containing GC B cells are known to be generated at inflammation sites in various pathologic conditions, such as autoimmunity, cancer, and allograft rejection ( 40 ), as well as in inflamed kidneys of several kidney diseases ( 34 , 41 , 42 ), we could not detect GC B cells in the kidney of 8-wo gddY mice, when IgA + PBs had already appeared. Therefore, IgA + PBs are possibly generated in GCs in some lymphoid organs or differentiated from their precursors, namely, memory B cells, which have undergone somatic hypermutation.…”
Section: Discussioncontrasting
confidence: 58%
“…However, the accumulation of somatic hypermutations in the IgA variable region genes cloned from these PBs suggests that they were generated via GCs in a T cell–dependent manner. Although tertiary lymphoid tissues containing GC B cells are known to be generated at inflammation sites in various pathologic conditions, such as autoimmunity, cancer, and allograft rejection ( 40 ), as well as in inflamed kidneys of several kidney diseases ( 34 , 41 , 42 ), we could not detect GC B cells in the kidney of 8-wo gddY mice, when IgA + PBs had already appeared. Therefore, IgA + PBs are possibly generated in GCs in some lymphoid organs or differentiated from their precursors, namely, memory B cells, which have undergone somatic hypermutation.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies have reported that TLTs are induced in various kidney diseases [62][63][64][65]. Additionally, we reported that TLTs developed not only in murine kidneys but also in human kidneys in an age-dependent manner [8].…”
Section: Clinical Significance Of Tertiary Lymphoid Tissues In Ckd and The Elderlymentioning
confidence: 66%
“…We searched PubMed for literature review and summarized clinical characteristics of 8 patients, including our case, in Table 1. [9][10][11][12][13][14][15] The average was 66 years old. There were 62.5% male patients.…”
Section: Discussionmentioning
confidence: 99%